Reconnaissance of Pharmaceuticals and Wastewater Indicators in Streambed Sediments of the Lower Columbia River Basin, Oregon and Washington1. (April 2014) - Nilsen, Elena; Furlong, Edward T.; Rosenbauer, Robert
Abstract One by‐product of advances in modern chemistry is the accumulation of synthetic chemicals in the natural environment. These compounds include contaminants of emerging concern (CECs), some of which are endocrine disrupting compounds (EDCs) that can have detrimental reproductive effects. The role of sediments in accumulating these types of chemicals and acting as a source of exposure for aquatic organisms is not well understood. Here we present a small‐scale reconnaissance of CECs in bed sediments of the lower Columbia River and several tributaries and urban streams. Surficial bed sediment samples were collected from the Columbia River, the Willamette River, the Tualatin River, and several small urban creeks in Oregon. Thirty‐nine compounds were detected at concentrations ranging from <1 to >1, 000 ng [g sediment]−1 dry weight basis. Concentrations and frequencies of detection were higher in tributaries and small urban creeks than in the Columbia River mainstem, suggesting a higher risk of exposure to aquatic life in lower order streams. Ten known or suspected EDCs were detected during the study. At least one EDC was detected at 21 of 23 sites sampled; several EDCs were detected in sediment from most sites. This study is the first to document the occurrence of a large suite of CECs in the sediments of the Columbia River basin. A better understanding of the role of sediment in the fate and effects of emerging contaminants is needed.